The impact of radical parotidectomy with immediate facial nerve reconstruction: a quality-of-life measure. Issue 9 (28th September 2021) - Subramaniam, N; Luu, E; Asher, R; Oates, J; Clark, J R; Low, T-H
Abstract: Objective: Immediate facial nerve reconstruction is the standard of care following radical parotidectomy; however, quality of life comparisons with those undergoing limited superficial parotidectomy without facial nerve sacrifice is lacking. Method: Patients who underwent parotidectomy were contacted to determine quality of life using the University of Washington Quality of Life and Parotidectomy Specific Quality of Life questionnaires. A total of 29 patients (15 in the radical parotidectomy and 14 in the limited superficial parotidectomy groups) completed and returned questionnaires. Results: Using the University of Washington Quality of Life Questionnaire, similar quality of life was noted in both groups, with the radical parotidectomy group having significantly worse speech and taste scores. Using the Parotidectomy Specific Quality of Life Questionnaire, the radical parotidectomy group reported significantly worse speech, eye symptoms and eating issues. Conclusion: Those undergoing radical parotidectomy with reconstruction had comparable overall quality of life with the limited superficial parotidectomy group. The Parotidectomy Specific Quality of Life Questionnaire better identified subtle quality of life complaints. Eye and oral symptoms remain problematic, necessitating better rehabilitation and more focused reconstructive efforts.